Integration of a Four-Step Reaction into One-Pot under the Coexistence of Silica-Gel-Supported Acid and Base Reagents: Synthesis of Benzo- and Naphthothiophenes Using NaHSO4/SiO2 and Na2CO3/SiO2 - Hayakawa, Mamiko; Aoyama, Tadashi; Nakaoka, Kyohei; Kosuge, Masayuki; Ouchi, Akihiko (Synthesis, 2019)
A four-step synthesis of benzo- and naphthothiophenes that have biological importance and application in material science was integrated into a one-pot reaction by using silica gel-supported acid and base reagents, NaHSO4/SiO2 and Na2CO3/SiO2. The supported reagents provided acid and base environments on the surface of the supports without neutralization and worked separately in the same medium. The four-step reaction comprises (i) deacetylation of 3-halo-2,4-pentanediones to α-halo ketones, (ii) deacetylation of S-aryl thioacetates to arenethiols, (iii) coupling of α-halo ketones and arenethiols to give α-sulfanyl ketones, and (iv) cyclization of sulfanyl ketones to benzo- and naphthothiophenes. The steps (i) and (iii) proceeded by Na2CO3/SiO2, and (ii) and (iv) by NaHSO4/SiO2. The four-step reaction proceeded efficiently by introduction of starting materials and reagents in a single reaction vessel. The starting materials were very easy to handle and unpleasant smell of aryl thiols that were used in conventional methods could be avoided. Novel thirty-nine benzo- and naphthothiophenes were synthesized by this method in excellent to fair yields.
Keywords: benzothiophenes; one-pot synthesis; 3-halo-2,4-pentanediones; S-aryl thioacetates; silica-gel-supported reagents